THE VENTRIS–CHADWICK CORRESPONDENCE AND THE DECIPHERMENT OF LINEAR B: A DENIER, A DISSENTER AND A DUBIOUS CONCLUSION. (December 2019) - Thompson, R. J. E.
Abstract : The correspondence between Michael Ventris and John Chadwick, housed in the Mycenaean Epigraphy Room in the Faculty of Classics, Cambridge, provides valuable insights into the decipherment of Linear B and the collaboration between the two men which produced first 'Evidence for Greek dialect in the Mycenaean archives' (Ventris and Chadwick (1953)) and then Documents in Mycenaean Greek (Ventris and Chadwick (1956)). The letters also reveal interesting information about the relationship between Ventris and Chadwick and other scholars of the day. This article examines their relationship with Arthur Beattie, who never accepted the decipherment, and Leonard R. Palmer, who disagreed fundamentally with many of their interpretations of the texts. A file of correspondence containing letters from 1956, discovered only after the publication of Andrew Robinson's biography of Ventris (Robinson (2002)), casts doubt on the conclusion that, perhaps in part owing to difficulties with Palmer, Ventris had lost interest in Linear B immediately before his death.